PENGARUH EFEKTIFITAS SISTEM INFORMASI AKUNTANSI DAN PENGENDALIAN INTERNAL TERHADAP KINERJA MANAJERIAL - Nia Ariska; Mulia Andirfa (LPPM STIE Lhokseumawe, 2019)
Managerial performance is the ability of managers in using knowledge, behaviors, and talents in performing their duties so as to achieve goals and tasks of the manager. This study aims to analyze the effect of Effectiveness of accounting information systems and internal control of Managerial Performance. The population of this research is PT PJB UBJOM PLTMG ARUN in Lhokseumawe accounting information system. Sampling technique using Census Sampling, obtained by 41 respondents and Data collection using questionnaire method. The results of this study indicate that the effectiveness of accounting information systems and internal control significant effect on Managerial Performance both partially and simultaneously.